Edison: His Life and Inventions - Dyer, Frank Lewis, 1870-1941; Martin, Thomas Commerford, 1856-1924 (Salt Lake City, UT : Project Gutenberg, 2006)
"Edison: His Life and Inventions" by Frank Lewis Dyer and Thomas Commerford Martin is a historical account likely written in the early 20th century. The narrative focuses on Thomas Alva Edison, one of America's most prolific inventors, and details his remarkable journey through life, marking his contributions to the field of electricity alongside the significant technological advancements occurring during his era. The opening of the book sets the stage by examining the socio-political climate of the mid-19th century when Edison was born, highlighting the flourishing age of electricity. It introduces Edison's lineage and early influences, portraying his childhood curiosity and the nurturing yet challenging environment he grew up in. The text stresses Edison's early fascination with science, particularly chemistry and electrical experiments, foreshadowing his future innovations. Through anecdotes, it illustrates Edison's relentless pursuit of knowledge, even at a young age, and hints at the trials he faced that shaped him into the groundbreaking inventor the world would come to admire. This early glimpse into Edison's life establishes the foundation for understanding his extraordinary contributions to modern technology. (This is an automatically generated summary.)
1910
Release date is 2006-01-21
Produced by Charles Keller and David Widger
Keywords: Edison, Thomas A. (Thomas Alva), 1847-1931; Inventors -- United States -- Biography